A Case of Tuberous Sclerosis with Subepedymal Giant Cell Astrocytoma without Classical Triad - 阿武 雄一; 瀧川 晴夫; 吉田 学; 福永 典子; 高橋 千春 (The Medical Journal of Matsue City Hospital, 2014)
Tuberous sclerosis (TSC) is a autosomal dominant multisystem neurocutaneous syndrome characterized by the development of multiple hamartomas distributed throughout the body, skin, brain and lungs. TSC had been diagnosed by classical triad as epilepsy, mental retardation and facial angiofibromas. Multimodal imaging can depict tumor spontaneously in asymptomatic case. We report a case of subependymal giant cell astrocytoma without any symptoms of the triad.